Effectiveness of Virtual Reality–Based START (Simple Triage and Rapid Treatment) Triage Education on Earthquake Preparedness Among Community Members - Nina Putri Calisanie, Nyayu; Ramdani, Ramdani; Fatimah, Sansa Anisa Nur (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Indonesia’s position along the Pacific Ring of Fire exposes it to frequent seismic events. The recent magnitude 5.6 earthquake in Cianjur highlighted notable deficiencies in community preparedness, especially in areas such as knowledge, disaster education, and emergency response planning. Insufficient public awareness remains a major obstacle to effective disaster risk management. Objective: This study aimed to determine the impact of Virtual Reality (VR)-based education using the Simple Triage and Rapid Treatment (START) method on enhancing earthquake preparedness among community members. Methods: A quasi-experimental design with pre- and post-tests and a control group was employed. A total of 112 participants were selected via purposive sampling and divided into intervention and control groups. The intervention group engaged in VR simulations focused on the START triage process as part of their disaster education curriculum. Knowledge improvement was measured using the N-Gain Score to evaluate pre- and post-intervention changes. Results: The VR-based START triage training led to a 64.47% increase in participants’ knowledge, reflecting a moderate level of effectiveness. Compared to the control group, those in the intervention group showed significantly greater improvements in earthquake preparedness. Conclusion: Incorporating START triage into VR-based educational programs can substantially boost community members’ understanding of earthquake preparedness. This interactive and scalable method holds promise for enhancing public disaster education and fostering greater resilience in vulnerable populations.